Maternal outcome in HELLP syndrome requiring intensive care management in a Turkish hospital - Osmanagaoglu, Mehmet Armagan; Osmanagaoglu, Selen; Ulusoy, Hülya; Bozkaya, Hasan (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Despite the de- velopment of tertiary care facilities, intensive care and advanced blood banking techniques, pregnancy-related hypertensive disorders are the main cause of maternal mortality in most coun- tries. Our purpose was to determine maternal outcome in pregnancies complicated by HELLP syndrome (hemolysis, elevated liver enzymes and low platelet count) that required intensive care management. DESIGN AND SETTING: Retrospective study at Department of Obstetrics and Gynecology, and Department of Anesthesiology and Reanimation, Karadeniz Technical University, Trabzon, Turkey. METHODS: 37 patients with HELLP syndrome admitted to the obstetric intensive care unit were analyzed retrospectively from 1992 to 2004. RESULTS: All patients were hypertensive, with mean Glasgow coma score (GCS) of 11 ± 3.96. Mean gestational age at delivery was 32 ± 4.09 weeks. Delivery was vaginally in nine and by cesarean section in 27 patients. General anesthesia was used in 12 and spinal anesthesia in 25 patients. Maternal morbidity included acute renal failure (11%), disseminated intravascular coagulation (5%), acute lung edema (3%), severe ascites (11%), pleural effusion (3%), adult respira- tory distress syndrome (11%), abruptio placenta (11%), cerebral edema (8%) and cerebral hemor- rhage (40%). All patients required transfusions using blood products. There were 11 maternal deaths (30%). CONCLUSION: Because of high maternal mor- tality and morbidity found among patients with HELLP syndrome, standard antenatal follow-up protocols should be applied, so as to obtain early diagnosis and improve the speed of transfer to obstetric departments with expertise in this field.